Generalization of scientific and institutional prerequisites for risk management of technological integration - A. E. Miller; L. M. Davidenko (Омский научный вестник: Серия "Общество. История. Современность")
The paper considers the key aspects of risk management in relation to the technological integration of economic entities. It is emphasized that the deepening of the technological chain includes the integration of resources of related production facilities and is undergoing changes in the context of accelerated digitalization, environmental transformation of the world economy. In this regard, the risk management system, which includes strategic mapping, systematization and risk assessment, as well as management control over financial, economic, scientific and technological types of risk, is of great importance. The authors highlight the trends of technological transformation of the global energy complex, which determine the promising directions of technological integration of the oil and gas sector for the development of carbon-neutral energy. As a positive vector, the development and implementation of innovations that improve environmental safety, as well as new technologies for the production of pure hydrogen from natural gas and recycling processes are shown. The conducted research allowed us to identify the scientific and institutional prerequisites for managing the risks of technological integration and to link them with risk management tools